2005
DOI: 10.1002/jcb.20518
|View full text |Cite
|
Sign up to set email alerts
|

Repair of DNA interstrand crosslinks may take place at the nuclear matrix

Abstract: Host cell reactivation assay using Trioxsalen-crosslinked plasmid pEGFP-N1 showed that human cells were able to repair Trioxsalen interstrand crosslinks (ICL). To study the mechanism of this repair pathway, cells were transfected with the plasmids pEGFP-1, which did not contain the promoter of the egfp gene, and with pEGFP-G-, which did not contain the egfp gene. Neither of these plasmids alone was able to express the green fluorescent protein. After cotransfection with the two plasmids, 1%-2% of the cells dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…It has been demonstrated that α IISp interacts with the nuclear matrix (Bachs et al 1990) and this observation is consistent with data demonstrating that the nuclear matrix may serve as an important locus for ICL repair (Atanassov et al 2005). …”
Section: Icl Repair In Quiescent Dnasupporting
confidence: 84%
“…It has been demonstrated that α IISp interacts with the nuclear matrix (Bachs et al 1990) and this observation is consistent with data demonstrating that the nuclear matrix may serve as an important locus for ICL repair (Atanassov et al 2005). …”
Section: Icl Repair In Quiescent Dnasupporting
confidence: 84%
“…Recent data have shown that the mechanisms involved in the process of nuclear foci formation include association of the HR proteins and the damaged chromatin to the underlying nuclear substructures. Sub-cellular fractionation experiments have shown that after treatment with ionizing radiation and DNA crosslinking agents Rad51, Rad54, BRCA1, BRCA2, FA proteins, and the BLM helicase were associated with the nuclear matrix fraction (Bischof et al, 2001;Qiao et al, 2001;Atanassov et al, 2005;Huber and Chodosh, 2005;Mladenov et al, 2006). The association of Rad51 with the nuclear matrix correlated with the formation of Rad51 nuclear foci and fractionation in situ confirmed that Rad51 foci remained firmly immobilized at the matrix (Mladenov et al, 2006).…”
Section: Discussionmentioning
confidence: 69%
“…Aggregation may prevent access to structures such as the nuclear matrix that may be required for repair (Mauldin et al, 2002;Atanassov et al, 2005). However, it is also possible that a delay in repair might accelerate aggregation, and clarification of the relationship between aggregation and repair awaits future study.…”
Section: Discussionmentioning
confidence: 95%